The Development of Arbitration Institutions in Resolving Sports Disputes: Challenges and Prospects - Agung Sujati Winata; Herliana Herliana; Dina Widyaputri Kariodimedjo (Universitas Islam Sultan Agung, 2026)
The development of sports as a complex industry has heightened the potential for disputes among stakeholders, including athletes, clubs, and sports organizations. This necessitates more efficient and professional dispute-resolution mechanisms. While sports arbitration has been recognized as a primary mechanism, the existence of arbitration institutions in Indonesia continues to face significant challenges, such as insufficient public awareness and understanding of arbitration institutions, persistent reliance on litigation, and a shortage of qualified human resources. This research aims to identify and analyze the challenges and opportunities confronting sports arbitration institutions in Indonesia. It serves as a foundation to formulate concrete strategies for strengthening their role in resolving sports disputes and enhancing their adaptability to global developments and international standards in sports dispute resolution. The study employs a normative legal research methodology, adopting a statutory approach to analyze relevant sports arbitration regulations and conducting a comprehensive literature. The findings of this study show that sports arbitration institutions, such as the Indonesian Sports Arbitration Body (BAKI), possess significant potential to resolve disputes effectively, particularly in fostering opportunities to establish a more competitive sports ecosystem. This potential stems from the inherent advantages of sports arbitration over conventional litigation in addressing sports-related conflicts, including its flexibility, the integration of digitalization and technology in advancing arbitration processes, inter-institutional collaboration, and the enhancement of arbitrator competencies, all of which can strengthen the national arbitration framework. Furthermore, while principles such as Lex Sportiva and Lex Ludica have been incorporated into Indonesia’s Sports Law as part of adapting to advancements in sports jurisprudence, inconsistencies persist due to overlapping jurisdictions between the autonomy of sports organizations and governmental oversight. This research contributes strategic recommendations to reinforce the national sports arbitration system, ensuring its alignment with global best practices and fostering institutional resilience in an evolving legal and sporting landscape.